FUNCTIONAL LITERACY AS AN EFFORT TO DEVELOP HOME BUSINESS FOR RURAL’S WOMEN IN SEMARANG-INDONESIA - Arbarini, Mintarsih; Jutmini, Sri; Joyoatmojo, Soetarno; Sutarno, (PEOPLE: International Journal of Social Sciences, 2020)
Rural’s women home business is very important considering that women are often the saviors of the family economy. This study aims to describe functional literacy as an effort to develop home business for rural’s women. The research method uses qualitative, in women's study groups. Data collection uses in this study consists of documentation, observation, and in-depth interviews. Qualitative descriptive method consists of data reduction, data presentation, and conclusion. The description of the results in this study shows functional literacy in learning groups can improve basic literacy and practical skills as an entrepreneurial development. The representation of women entrepreneurs is still relatively low which can be attributed to factors such as low level of education, lack of capital, and cultural. The development of effective home business is carried out continuously and simultaneously through functional literacy which has implications for improving the economy and family welfare. The application of functional literacy is to develop a woman's home business, so it will build a potential business center such as food stalls, various handicrafts, and the utilization of natural potential around. The development of women's home business in rural areas has become more prosperous and has a better livelihood. Home business Development has been conducted with various activities ranging from functional literacy activities to various skills required by poor women in rural areas.